The Use of Educational Puzzle Games for the Development of Cognitive Abilities of Children Aged 5-6 Years - Nazilah, Mahdatu Bayatina; Rahmah, Miftah fadhilah; Aliza, Nur; Salianty, Syariah (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
Development in early childhood is the most critical thing in children's future growth, and child development will also determine when children grow up. One aspect of child development that is important to develop is the cognitive aspect. An exciting method is needed to stimulate the spatial abilities as well as fine motor skills of children. One of them is a Puzzle game. Children's cognitive development can increase optimally by playing a Puzzle game tool because they have to solve puzzles from Puzzle pieces to form the appropriate image pattern. This study was conducted using a qualitative approach, descriptive type, where the goal is to observe and understand the behavior of children or groups in certain situations without being known by the child to see if there are differences in the optimization of cognitive development between each child. Based on the results of research that has been done, Puzzle educational games can stimulate early childhood cognitive development. It is shown by the fact that most of the children observed could put the Puzzle pieces back together into a suitable shape. They can also coordinate eyes and hands in the process of joining Puzzle parts and identifying geometric shapes well. Abstrak Perkembangan pada masa anak-anak adalah hal yang paling penting pada pertumbuhan anak di masa mendatang, perkembangan anak juga akan menentukan saat anak beranjak dewasa. Salah satu aspek dalam perkembangan anak yang penting untuk dikembangkan ialah aspek kognitif. Untuk mengembangkannya diperlukan metode yang menarik dan mampu merangsang kemampuan spasial sekaligus keterampilan motorik anak dengan baik. Salah satunya ialah dengan permainan papan Puzzle. Dengan memainkan alat permainan Puzzle perkembangan kognitif anak dapat bertambah optimal, karena harus memecahkan masalah dari potongan-potongan Puzzle agar membentuk pola gambar yang sesuai. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif jenis deskriptif, di mana tujuannya ialah untuk mengamati dan memahami perilaku anak atau kelompok dalam situasi tertentu, tanpa diketahui oleh anak agar dapat melihat apakah ada perbedaan optimalisasi perkembangan kognitif antara masing-masing anak. Berdasarkan hasil penelitian yang telah dilakukan, bahwa permainan edukatif Puzzle mampu merangsang perkembangan kognitif anak usia dini. Hal ini ditunjukkan dengan fakta bahwa sebagian besar dari anak-anak yang diamati mampu menyatukan kembali potongan-potongan Puzzle tersebut menjadi bentuk yang sesuai. Mereka juga mampu mengkoordinasikan mata dan tangan dalam proses penyatuan bagian-bagian Puzzle serta mengidentifikasi bentuk geometri dengan baik.